THE INFLUENCE OF PHYSICAL FACTORS ON THE GROWTH OF BACTERIA-ANTAGONIST BACILLUS SUBTILIS BIM B-760 D - Kuptsov, V.N.; Shmyga, E.Y.; Kolomiets, E.I.; Nagorny, R.K.; Plavsky, V.U. (Eurasian Journal of Applied Biotechnology, 2023)
The influence of electric current and electromagnetic radiation on the growth and antimicrobial activity of bacteria B. subtilis BIM B-760 D - the basis of the biopesticide "Bactaven C" was studied. It was determined that the use of inoculum treated with an alternating current of 16 mA and frequency 17 Hz has enabled to obtain a 2-day culture of B. subtilis BIM B-760 D with a titer of CFU and spores 2.4 – 2.7 times higher compared to the variant without electrical stimulation. Exposure of the seed material for 30 minutes in the electromagnetic field of a Tesla transformer (frequency 490 kHz) with a multi–needle electrode promoted 1.9 – 2.0 times increase in the titer of spores, CFU and 12 % higher antifungal activity by 48 h of culture.